Triacylglycerol composition of walnut (Juglans regia L.) cultivars: Characterization by HPLC-ELSD and chemometrics - Amaral, Joana S. (2004)
A total of 26 walnut ( Juglans regia L.) samples from 9 cultivars (Arco, Franquette, Hartley, Lara, Marbot, Mayette, Mellanaise, Parisienne, and Rego) harvested in the 2001, 2002, and 2003 crop years and grown in two geographical origins (Bragancüa and Coimbra, Portugal) were evaluated with regard to their triacylglycerol composition. The methodology employed was reversed-phase highperformance liquid chromatography coupled to an evaporative light-scattering detector (RP-HPLCELSD) after extraction of the lipidic fraction of the nuts. Nine compounds were separated, identified, and quantified. All samples presented an identical qualitative profile composed by LLnLn, LLLn, LLL, OLLn, OLL, PLL, OOL, and PLO (P ) palmitoyl; O ) oleoyl; L ) linoleoyl; Ln ) linonenoyl). Trilinolein (LLL) was the major triglyceride, followed by dilinoeoyl-oleoyl-glycerol (OLL) and dilinoleoyl-linolenoylglycerol (LLLn), with mean values of 37.7, 18.5, and 18.4%, respectively. Significant differences in composition were found between cultivars, and these differences were also significant when cultivars were grouped by year of production, showing that besides genetic factors, the triacylglycerol composition can be strongly influenced by environmental factors.